2013
DOI: 10.1371/journal.pone.0074496
|View full text |Cite
|
Sign up to set email alerts
|

Four Decades of Andean Timberline Migration and Implications for Biodiversity Loss with Climate Change

Abstract: Rapid 21st-century climate change may lead to large population decreases and extinction in tropical montane cloud forest species in the Andes. While prior research has focused on species migrations per se, ecotones may respond to different environmental factors than species. Even if species can migrate in response to climate change, if ecotones do not they can function as hard barriers to species migrations, making ecotone migrations central to understanding species persistence under scenarios of climate chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 34 publications
1
55
0
Order By: Relevance
“…A progressively warmer climate would induce these plants to migrate, probably vertically from low-lying areas to higher areas (Foster 2001). Recent studies support this hypothesis in Peru (Feeley et al 2011, Lutz et al 2013, Venezuela (Safont et al 2012) and Colombia (Reina-Rodríguez et al 2016). The data herein supported estimates of altitudinal changes of 177.5 m (present-2030) and 379.8 m (present-2050) for the 12 focal species.…”
Section: Discussionsupporting
confidence: 80%
“…A progressively warmer climate would induce these plants to migrate, probably vertically from low-lying areas to higher areas (Foster 2001). Recent studies support this hypothesis in Peru (Feeley et al 2011, Lutz et al 2013, Venezuela (Safont et al 2012) and Colombia (Reina-Rodríguez et al 2016). The data herein supported estimates of altitudinal changes of 177.5 m (present-2030) and 379.8 m (present-2050) for the 12 focal species.…”
Section: Discussionsupporting
confidence: 80%
“…In the search for colder climates they may reduce their range size (Buermann et al, 2011;La Sorte and Jetz, 2010) and suffer population declines (Shoo et al, 2005;Harris et al, 2014). Indeed, in the last 42 years the mountain plant species in Peru have been migrating in altitude (Lutz et al, 2013), and birds have been moving gradually (Forero-Medina et al, 2011a). Although this study did not predict the disappearance of climate envelopes for bird species (total reduction of geographic range), which increases the likelihood of extinction (Williams et al, 2007), high percentages of range losses were predicted.…”
Section: Changes In Geographic Distribution and Conservationmentioning
confidence: 61%
“…In what we believe to be the most detailed assessment of tropical treeline shifts in any region to date, Lutz et al () found that only 18% of the treeline segments that they examined in Peru had shifted upslope over a 42 yr study period. The majority of treelines that shifted upslope were located within protected areas relatively‐free from human impacts.…”
Section: Past and Present Tropical Treeline Shifts And Conditionsmentioning
confidence: 93%